1984
DOI: 10.1115/1.3231028
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Boundary Layer Velocity Gradients and Bed Proximity on Vortex Shedding From Free Spanning Pipelines

Abstract: The paper summarizes the results of a laboratory study of the separate and combined effects of bed proximity and large velocity gradients on the frequency of vortex shedding from pipeline spans immersed in the thick boundary layers of tidal currents. This investigation forms part of a wider project concerned with the assessment of span stability. The measurements show that in the case of both sheared and uniform approach flows, with and without velocity gradients, respectively, the Strouhal number defining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 0 publications
6
51
2
Order By: Relevance
“…They also measured velocity fluctuations in the near wake of the cylinder to study the effect of h / d on the Strouhal number of the vortex shedding, St, and reported that the critical gap ratio ͑h / d͒ c , at which the spectral peak of the local velocity fluctuations disappeared, was 0.2-0.3 ͑it should be noted, however, that the disappearance of the spectral peak of the local velocity fluctuations does not necessarily ensure the global cessation of the vortex shedding 5 ͒. Similar measurements of local velocity fluctuations and thereby of ͑h / d͒ c were also carried out at higher and lower Reynolds numbers, [6][7][8] whereas more details of the global cessation of the Kármán vortex shedding were later visualized but only at lower Reynolds numbers, 5,9,10 as summarized in Table I.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…They also measured velocity fluctuations in the near wake of the cylinder to study the effect of h / d on the Strouhal number of the vortex shedding, St, and reported that the critical gap ratio ͑h / d͒ c , at which the spectral peak of the local velocity fluctuations disappeared, was 0.2-0.3 ͑it should be noted, however, that the disappearance of the spectral peak of the local velocity fluctuations does not necessarily ensure the global cessation of the vortex shedding 5 ͒. Similar measurements of local velocity fluctuations and thereby of ͑h / d͒ c were also carried out at higher and lower Reynolds numbers, [6][7][8] whereas more details of the global cessation of the Kármán vortex shedding were later visualized but only at lower Reynolds numbers, 5,9,10 as summarized in Table I.…”
Section: Introductionmentioning
confidence: 79%
“…It might still be possible to argue that the very thin boundary layer locally developed on the moving ground generates vorticity of opposite sign and thus to interfere with the separated shear layer from the bottom side of the cylinder, just like the cases with a thick boundary layer formed on a fixed ground. 8,24 Judging from the mean spanwise vorticity contours ͓cf. Figs.…”
Section: -7mentioning
confidence: 99%
“…The fundamental effects of gap ratio have been observed by Taneda (1965), Roshko et al (1975), Bearman and Zdravkovich (1978), Burest and Lanciotti (1979), Angrilli et al (1982), Grass et al (1984), Zdravkovich (1985a), Price et al (2002) and Lin et al (2005).…”
Section: Introductionmentioning
confidence: 83%
“…There are a number of publications on experiments aimed at studying the effect of a boundary on the fluidstructure interaction forces for the case of stationary cylinders [13][14][15][16][17][18]. Important conclusions of these studies are that vortex shedding is suppressed for gaps smaller than one third of the cylinder's diameter, and that there is a mean cross-flow force that pushes the cylinder away from the boundary.…”
Section: Introductionmentioning
confidence: 99%